REGIONAL LEVEL EVALUATION OF ACCIDENT-PRONE ROAD SECTIONS: A CASE STUDY OF THE MANDALAWANGI–PANDEGLANG HIGHWAY KM 18–KM 28 - Muhammad Oka Mahendra; Azani Musyarof (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Traffic accidents on the Mandalawangi–Pandeglang Highway, particularly on the Km 18–Km 28 segment, have become a serious concern due to the high number of accidents recorded in the 2020–2024 period, with a total of 100 incidents resulting in 186 victims, including 32 deaths, 20 serious injuries, and 134 minor injuries. This study was conducted to evaluate the level of accident vulnerability by applying the Equivalent Accident Number (EAN) method to measure the severity of accidents based on the weight of victims, as well as the Upper Control Limit (BKA) and Upper Control Limit (UCL) methods as statistical limits in identifying blackspot locations. The analysis results show that three road segments, namely Km 18 (EAN=375), Km 19 (EAN=222), and Km 22 (EAN=93), are included in the blackspot category because their EAN values exceed the BKA (110) and UCL (118) thresholds, with dominant causal factors including poor road geometric conditions (sharp bends and steep descents), lack of street lighting, undisciplined driver behavior (such as violating traffic signs and high speeds), and unroadworthy vehicles. Based on these findings, this study recommends a series of corrective actions, including the installation of clearer warning signs and road markings, increased lighting at vulnerable points, improved road geometric design, stricter law enforcement against traffic violations, and safety education campaigns for road users, in order to reduce the number of accidents and create a safer and more sustainable transportation environment in the future.